Psychological disorders and suicide attempts in youths during the pre-COVID and post-COVID era in a Taiwan pediatric emergency department - Guo, Bei-Cyuan; Chen, Ying-Ju; Huang, Wun-Yan; Lin, Mao-Jen; Wu, Han-Ping (Frontiers in Psychology, 2023)
The COVID-19 pandemic has had a significant impact on pediatric patients, increasing their vulnerability to psychological fragility. The aim of this study was to investigate the epidemiology and clinical spectrum of pediatric psychological fragility and suicide attempts in the emergency department (ED) before and after the onset of the COVID-19 outbreak.Methods: A total of 340 pediatric patients admitted to the ED for psychological fragility between 2019 and 2022 were retrospectively collated and categorized according to three periods: pre pandemic, pandemic, and post pandemic. Epidemiological and clinical information were analyzed and compared among the three groups. Moreover, patients with suicidal ideation or suicidal attempts and types of substance use disorders in children with suicidal attempts sent to the ED were analyzed.The proportion of psychological fragility increased during the pandemic period (0.4%) and the post-pandemic period (0.8%) compared to that in the pre-pandemic period (0.28%). Suicide ideation was the highest before the pandemic period (0.04%), while suicidal attempts were the highest in the post pandemic period (0.42%). Significantly elevated trends in suicide attempts involving overdose and injury were observed among the three groups (P<0.05). Intensive care unit (ICU) admission rates increased significantly after the COVID-19 outbreak (P<0.05), and major depressive disorder was the most common psychological fragility in the ED in all three groups.Conclusions: An increase in the proportion of pediatric psychological fragility in the ED was noted in the post pandemic period than before or during the pandemic. With higher rates of ICU admissions and an increase in suicide attempts among children and adolescents during the pandemic compared to before or after the pandemic, it is of utmost importance to provide mental health support to this vulnerable population in order to prevent suicide attempts in the 3 event of a new global outbreak of infectious diseases.